Tsukamurella tyrosinosolvens Respiratory Infection in Immunocompetent Man - Aidan Clifford; Jenny Siaw Jin Wong; Ben Aw-Yeong; Kerrie Lea; Maria Globan; Benjamin Smith (Emerging Infectious Diseases)
Tsukamurella spp. are an infrequent and underdiagnosed cause of bacterial respiratory infection, usually occurring in patients with structural lung disease or immune compromise. We describe T. tyrosinosolvens respiratory infection in a patient in Australia without structural lung disease or known immune deficiency. The patient was successfully treated with oral ciprofloxacin and clarithromycin.